Residual aluminium in drinking water supplies in relation to peatland catchment areas in Mukah, Sarawak - Eklip, Mildred (Universiti Malaysia Sarawak, (UNIMAS), 2014)
This study was focused on the relationship between peatland catchment areas and A1 with the aim of providing a better understanding on how A1 occurrences in natural ecosystem had impacted treated water supply. For some major development areas in Sarawak, the only available water sources are of peat waters. The peatland areas of the state's coastal zones are often characterized by high S²- contents and Fe A1 complexes. Thus, the objectives of this study were to; (1) quantify teh levels of A1 and other trace metals in raw and treated water from peat and non-peat sources and 2) quantify the levels of organic matter and nutrients in raw water from from peat and non-peat sources.